Immunochemical analysis of poly(ADP-ribosyl)ation in HaCaT keratinocytes induced by the mono-alkylating agent 2-chloroethyl ethyl sulfide (CEES): Impact of experimental conditions. (26th February 2016) - Debiak, Malgorzata; Lex, Kirsten; Ponath, Viviane; Burckhardt-Boer, Waltraud; Thiermann, Horst; Steinritz, Dirk; Schmidt, Annette; Mangerich, Aswin; Bürkle, Alexander
Highlights: Biological effects of CEES-treated cells are significantly influenced by treatment protocol. Optimized protocol for the treatment of HaCaT cells with CEES. CEES induces a dose- and time-dependent PARylation response in HaCaT cells. CEES-induced PAR formation is predominantly due to the activation of PARP1. Abstract: Sulfur mustard (SM) is a bifunctional alkylating agent with a long history of use as a chemical weapon. Although its last military use is dated for the eighties of the last century, a potential use in terroristic attacks against civilians remains a significant threat. Thus, improving medical therapy of mustard exposed individuals is still of particular interest. PARP inhibitors were recently brought into the focus as a potential countermeasure for mustard-induced pathologies, supported by the availability of efficient compounds successfully tested in cancer therapy. PARP activation after SM treatment was reported in several cell types and tissues under various conditions; however, a detailed characterization of this phenomenon is still missing. This study provides the basis for such studies by developing and optimizing experimental conditions to investigate poly(ADP-ribosyl)ation (PARylation) in HaCaT keratinocytes upon treatment with the monofunctional alkylating agent 2-chloroethyl ethyl sulfide ("half mustard", CEES). By using an immunofluorescence-based approach, we show that optimization of experimental conditions with regards to the type of solvent, dilution factors and treatment procedure is essential to obtain a homogenous PAR staining in HaCaT cell cultures. Furthermore, we demonstrate that different CEES treatment protocols significantly influence the cytotoxicity profiles of treated cells. Using an optimized treatment protocol, our data reveals that CEES induces a dose- and time-dependent dynamic PARylation response in HaCaT cells that could be completely blocked by treating cells with the clinically relevant pharmacological PARP inhibitor ABT888 (also known as veliparib). Finally, siRNA experiments show that CEES-induced PAR formation is predominantly due to the activation of PARP1. In conclusion, this study provides a detailed analysis of the CEES-induced PARylation response in HaCaT keratinocytes, which forms an experimental basis to study the molecular mechanism of PARP1 activation and its functional consequences after mustard treatment in general. Such a study is presented in an accompanying article (Mangerich et al., 2016 ).